Effects of ionizing radiation on the immune system with special emphasis on the interaction of dendritic and T cells - Manda, Katrin; Glasow, Annegret; Paape, Daniel; Hildebrandt, Guido (Frontiers in Oncology, 2012)
Dendritic cells (DCs), as professional antigen-presenting cells, are members of the innate immune system and function as key players during the induction phase of adaptive immune responses. Uptake, processing, and presentation of antigens direct the outcome toward either tolerance or immunity. The cells of the immune system are among the most highly radiosensitive cells in the body. For high doses of ionizing radiation (HD-IR) both immune-suppressive effects after whole body irradiation and possible immune activation during tumor therapy were observed. On the other hand, the effects of low doses of ionizing radiation (LD-IR) on the immune system are controversial and seem to show high variability among different individuals and species. There are reports revealing that protracted LD-IR can result in radioresistance. But immune-suppressive effects of chronic LD-IR are also reported, including the killing or sensitizing of certain cell types. This article shall review the current knowledge of radiation-induced effects on the immune system, paying special attention to the interaction of DCs and T cells.